2003
DOI: 10.1097/00000374-200301000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Alcohol-Associated Colonic Hyperregeneration by ??-Tocopherol in the Rat

Abstract: Alcohol-associated hyperproliferation could be prevented, at least in part, by supplementation with alpha-tocopherol. This may support the hypothesis that free radicals are involved in the pathogenesis of alcohol-associated colorectal hyperproliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 49 publications
0
6
0
1
Order By: Relevance
“…The association with alcohol intake is intriguing, as alcohol intake has been convincingly associated with an increased risk of colorectal cancer, especially for men 17 . In support of this association, increased cell regeneration and proliferation has been observed in experimental animals treated with ethanol as well as in chronic alcoholic patients 43-45 . These effects of alcohol have been hypothesized to be medicated through prostaglandin production (via COX), lipid peroxidation, generation of reactive oxygen species, and proinflammatory cytokine induction 17,46,47 .…”
Section: Discussionmentioning
confidence: 63%
“…The association with alcohol intake is intriguing, as alcohol intake has been convincingly associated with an increased risk of colorectal cancer, especially for men 17 . In support of this association, increased cell regeneration and proliferation has been observed in experimental animals treated with ethanol as well as in chronic alcoholic patients 43-45 . These effects of alcohol have been hypothesized to be medicated through prostaglandin production (via COX), lipid peroxidation, generation of reactive oxygen species, and proinflammatory cytokine induction 17,46,47 .…”
Section: Discussionmentioning
confidence: 63%
“…In this study, Tween 80 was chosen because: (i) it allows the preparation of a water-soluble mixture, which was suitable in order to improve gastrointestinal absorption and (ii) it was used in other studies (Krishnamurthy & Bieri, 1963;Ilavazhagan et al, 2001) without any adverse effects. Unfortunately, since Tween reduced Nrf2, suggesting a pro-oxidant effect, the antioxidant (Krishnamurthy & Bieri, 1963;Ilavazhagan et al, 2001;Kalender et al, 2004) and/or antiproliferative (Vincon et al, 2003) effects of vitamin E could not be properly evaluated in this study. Furthermore, our findings indicate that signaling for cell proliferation occurs by means of hydrogen peroxide in oral mucosa, which is in accordance with previous studies in other tissues (Burdon, 1995;Li & Spector, 1997).…”
Section: Correlation Of Cell Proliferation and Oxidative Parametersmentioning
confidence: 93%
“…A lower grade of keratinization and a longer contact with the ingested alcohol may also contribute to this effect. Vincon et al (2003) reversed the increase in alcoholrelated proliferation in the colon mucosa of rats by means of vitamin E supplementation. In our study, the protective effects of vitamin E were found only in terms of attenuation of alcohol-related decrease in Nrf2 immunocontent.…”
Section: Ventral Tongue Mucosamentioning
confidence: 97%
See 1 more Smart Citation
“…Yet, some of these effects have been described using the Caco-2 colorectal carcinoma cell line (8), which do not express any ADH (13), suggesting that one or several other metabolic pathways could play a role in the tumor-promoting activity of ethanol. As an example, free radicals generated from ethanol metabolism are thought to play a role in the pathogenesis of alcohol-associated colorectal hyperproliferation (14). Furthermore, ethanol could also undergo chemical coupling to membrane phospholipids via the action of phospholipase D (PLD; refs.…”
Section: Introductionmentioning
confidence: 99%